Early neonatal outcomes in infants of mothers with organ transplantation under immunosuppressive treatment - Kıymet Çelik; Sema Arayıcı; Nurten Özkan Zarif; Zeynep Kıhtır; Hakan Ongun; Bülent Aydınlı (The Turkish Journal of Pediatrics)
Background. This study aimed to examine early clinical and laboratory findings in infants born to mothers who had organ transplants and received immunosuppressive treatment.